Biomechanical analysis of a novel bone cement bridging screw system combined with percutaneous vertebroplasty for treating Kummell’s disease - Zhan, Yi; Bao, Chang; Yang, Huiming; Li, Liang; Yan, Liang; Kong, Lingbo; Hao, Dingjun; Wang, Biao (Frontiers in Bioengineering and Biotechnology, 2023)
Kummell’s Disease (KD) was originally proposed by Dr. Hermann Kummell in 1891 as a type of delayed posttraumatic vertebral collapse, which is a clinical phenomenon.The purpose of this experiment is to compare the strength of bone cement and the novel bone cement bridging screw in the treatment of thoracolumbar Kummell disease (KD) with other treatment methods. Thirty sheep spine specimens were selected. T12 to L2 segments were selected, and a KD intravertebral vacuum cleft model was made at the L1 segment. According to the ways of cement filling, the specimens were divided into percutaneous vertebroplasty (PVP), PVP combined with unilateral percutaneous pediculoplasty (PPP), PVP combined with bilateral PPP, unilateral novel bone cement bridging screw system combined with PVP, and bilateral cement bridging screw system combined with PVP groups. There were two experiments: three-dimensional biomechanical strength test and axial compression test. In the three-dimensional biomechanical strength test, we measured the strength of bone cement in specimens under six motion states, including flexion, extension, left bending, right bending, and left and right axial rotations. In the axial compression test, we detected the maximum axial pressure that the bone cement could withstand when it was under pressure until the bone cement was displaced. The unilateral or bilateral novel bone cement bridging screw with PVP groups had the best strength under flexion, extension, left bending, right bending, and had better biomechanical strength, with a significant difference from the other three groups (P < 0.05). There was no significant difference between the unilateral or bilateral novel bone cement bridging screw with PVP groups (P > 0.05). Unilateral and bilateral novel bone cement bridging screw could achieve similar bone cement strength. Compared with the other three groups, the unilateral or bilateral novel bone cement bridging screw with PVP groups are higher 136.35%, 152.43%; 41.93%, 51.58%; 34.37%, 43.50% respectively. The bilateral novel bone cement bridging screw with PVP could bear the largest pressure under vertical force. To conclude, the novel bone cement bridging screw can increase the strength of bone cement and avoid the loosening and displacement of bone cement in the treatment of KD of the